In situ multiscale study of deformation heterogeneities in polylactide‐based materials upon drawing: Influence of initial crystallinity and plasticization. Issue 21 (23rd September 2018) - Brüster, Berit; Martin, Arnaud; Bardon, Julien; Koutsawa, Yao; Bernstorff, Sigrid; Raquez, Jean‐Marie; André, Stéphane; Dubois, Philippe; Addiego, Frédéric
ABSTRACT: This work aims at identifying defects called deformation heterogeneities developing in polylactide (PLA)‐based materials upon drawing at room temperature. The influence of the initial crystallinity and of the plasticization methodology (physical blending vs. reactive blending) on the type of defect is also investigated. Defects are characterized in situ by (a) calculating the volume strain from digital image correlation (DIC), (b) measuring their surface density from optical microscopy, and (c) assessing their scattering invariant from small‐angle X‐ray scattering. Complementary structural analyses are done by microcomputed X‐ray tomography and atomic force microscopy. Drawing is accompanied by crazing in the case of low‐crystalline PLA, cracking in the case of annealed PLA, no defect in the case of plasticized PLA by physical blending, and shear bands and cracking in the case of plasticized PLA by reactive blending. These observations are discussed based on the initial structural features of the materials. © 2018 Wiley Periodicals, Inc. J. Polym. Sci., Part B: Polym. Phys.2018, 56, 1452–1468 Abstract : Defects developing in PLA‐based materials upon drawing are studied by a multiscale and in situ approach. Low crystalline PLA exhibits crazing, while after annealing, tortuous defects are noted. These defects may be induced by the opening of crystallization‐induced cracks. Physical plasticization of PLA engenders no defect, while reactive plasticization of PLA induces shear bands and localized cracks. A multiscale correlation of defect characterization is performed in the case of crazing, showing the relevancy of this approach.